Bundling in a Distribution Channel with Retail Competition - Heinzel, Joachim Maria Josef
We analyze the incentives for retail bundling and the welfare effects of retail bundling in a decentralized distribution channel with two retailers and two monopolistic manufacturers. One manufacturer exclusively sells his good to one retailer, whereas the other manufacturer sells his good to both retailers. Thus, one retailer is a monopolist for one product but competes with the other retailer in the second product market. The two-product retailer has the option to bundle his goods or to sell them separately. We find that bundling aggravates the double marginalization problem for the bundling retailer. Nevertheless, when the retailers compete in prices, bundling can be more profitable than separate selling for the retailer as bundling softens the retail competition. The ultimate outcome depends on the manufacturers’ marginal costs. Given retail quantity competition, however, bundling is in no case the retailer’s best strategy. Furthermore, we show that profitable bundling reduces consumer and producer surplus in the equilibrium.
Keywords: retail bundling; leverage theory; double marginalization